SYNTHESIS AND CHARACTERIZATION OF SUSTAINABLE POLYMER FOR CO2 CAPTURE - MAMAT, MUHAMMAD ISMAIL (2023)
Carbon Dioxide (CO2) emissions are a major problem that has been facing by the world. The increasement of the CO2 concentration in the atmosphere has been leading to the world temperature increasing.